2017
DOI: 10.1080/1061186x.2017.1363211
|View full text |Cite
|
Sign up to set email alerts
|

Covalent immobilisation of transglutaminase: stability and applications in protein PEGylation

Abstract: Microbial transglutaminase enzyme (mTGase) is an extremely useful enzyme that is increasingly employed in the food and pharmaceutical industries and as a tool for protein modification and tagging. The current study describes how we immobilised mTGase (iTGase) on a solid support to improve its stability during the PEGylation process by which polyethylene glycol chains are attached to protein and peptide drugs. When the enzyme was immobilised at the N-terminal sequence on agarose beads, it retained more than 53%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Then its activity decreased to 426 U/g (26% of the initial activity) after 10 cycles. Both of the immobilized trypsin and TGase showed better operational stabilities than other papers reported [43][44][45]. Overall, this DEL film can be repeatedly used for four cycles without obvious activity decrease.…”
Section: Resultsmentioning
confidence: 68%
“…Then its activity decreased to 426 U/g (26% of the initial activity) after 10 cycles. Both of the immobilized trypsin and TGase showed better operational stabilities than other papers reported [43][44][45]. Overall, this DEL film can be repeatedly used for four cycles without obvious activity decrease.…”
Section: Resultsmentioning
confidence: 68%
“…It has been demonstrated that mTGase is a valuable tool for protein derivatization and polymer modification since it is possible to select the coupling to complete the reaction at either lysine or glutamine residues depending on the PEG substrate used; in both cases there is high site‐selective specificity. Additionally, we showed that immobilized mTGase on agarose beads is still active and able to form site selective conjugates, thus simplifying the purification of the conjugate from mTGase (Grigoletto, Mero, Yoshioka, Schiavon, & Pasut, 2017). The enzymatic tool of protein derivatization can be applied not only to polymer conjugation to proteins, but also to other applications such as protein labeling or small molecule drug conjugation.…”
Section: Polymer Conjugation For Biotech Drugsmentioning
confidence: 99%
“…Numerous approaches have been developed to partially solve the obstacles above and increase the delivery efficiency of proteins/peptides [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. For example, covalent conjugation of a nontoxic polymer, typically poly(ethylene glycol) (PEG) to a protein, named PEGylation, can effectively extend the circulating half-life and increase the stability of the protein [ 7 , 21 , 22 ]. Many PEGylated protein therapeutics, such as PEG-interferon α-2a (PEG-IFNα-2a), PEG- l -asparaginase, PEG-adenosine deaminase, PEG-uricase and PEG-tumor necrosis factor alpha (PEG-TNFα), PEG-continuous erythropoietin receptor activator (PEG-CREA) have been applied in clinic and exhibit better pharmaceutical profiles compared to the unmodified forms [ 7 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%